X overtakes WeChat in spreading Chinese disinformation about the 2024 US presidential elections - Oiwan Lam (Global Voices, 2024)
New research indicates that X, formerly Twitter, has overtaken WeChat, the most popular Chinese social media platform, in spreading disinformation about the US presidential elections and policies.
China